An Assessment of Local People’s Support to Private Wildlife Conservation: A Case of Save Valley Conservancy and Fringe Communities, Zimbabwe - Given Matseketsa; Billy B. Mukamuri; Never Muboko; Edson Gandiwa (Scientifica)
The long-term survival of a protected area (PA) may depend to a greater extent on the goodwill and support of the people residing around it. This study assessed local people’s support for private sector driven wildlife conservation in Zimbabwe, using the Save Valley Conservancy (SVC) as a case. Specifically, the objectives of the assessment were threefold: (i) to establish perceptions on the current nature of the relationship between SVC and people living on its edge, (ii) to ascertain the proximate and underlying causes of local resistance to SVC, and (iii) to identify strategies local people employ to resist SVC conservation efforts. Data were collected through a household questionnaire survey during the month of April, 2018. In addition, photographs showing the nature of vandalism and sabotage imposed on the SVC ecosystem by fringe communities were also collected, as part of evidential data. A multistage sampling method was adopted, and this combined purposive sampling to select study wards: random sampling to select villages and systematic sampling to select households (n=71). Our results show that local people rate the current relationship between them and SVC owners as bad, i.e., undesirable interaction. The nature of this perceived bad relationship is attributed to a host of factors, key among them being, lack of wildlife-related benefits and escalation of wildlife-induced costs, which are crucial in determining local community’s support for conservation. We conclude that the studied local community’s support for private nature conservation is marginal; hence, there is a need for increased efforts by SVC owners to devise realistic incentives including an active engagement of local communities so that they cooperate with conservation efforts.